THE EFFECT OF SCAFFOLDING STRATEGY ON MATHEMATICAL PROBLEM - SOLVING ABILITY REGARDING LINEAR EQUATIONS - Titin Anisa Tanjung; Fibri Rakhmawati (FKIP Universitas Muhammadiyah Tangerang, 2026)
This study aims to the determine the effect of the scaffolding strategy on studendts mathematical problem - solving abilities and to examine these abilities before and after the implementation of the strategy inan eight- grade class at an MTs (Islamic Junior High School). The Study employs apre - exprimental design specifically,a one -group pretest - posttest design using a quantitative approach. The sample consists of eight - grade students at MTs Al - Washliyah Pasar Miring. Statistical analysist was used to assess the impact of the scaffolding strategy on the students mathematical problem-solving skills. The analysist results indicate a positive effect of the scaffolding strategy on the students mathematical problem - solving abilities.